Perancangan Interior Rumah Usiawan Panti Surya di Surabaya - Yohan Santoso, Novita Kumalasari Mariana Wibowo (Intra, 2014)
The advance of century and technology in Indonesia however triggered the social changes in society. One of the social changes is the pattern of relationship between parents and their children, especially the urban society. The hectic activity and high individualism are the causes that made parents rarely get proper attention and care from their children. A lot of parents are left even separated from their childrens life. This phenomenon will greatly affect the mental and psychological development of parents. People in the elder stage will feel that they are useless if they do not get any attention that they need. This design interior of Panti Surya Orphanage aim to fulfill the needs by parents who do not get proper care from their children and live lonely. This interior design using an analytical method with doing field survey and direct interview to know what the real problem is, and then collecting the data that are gathered and analyze the data as the fundamental of the design. The orphanage design is based on the Universal Design standard so that this design can give a good impact to the elders and the society around.